Should SME exposures be treated as retail or corporate exposures? A comparative analysis of default probabilities and asset correlations in French and German SMEs - Dietsch, Michel; Petey, Joël (Journal of Banking & Finance, 2004)
We use a one-factor credit risk model to provide new estimates of stationary default probabilities and asset correlations in two large samples of French and German Small and Medium-sized Enterprises. Results show that, on average, SMEs are riskier than large businesses; and the asset correlations in the SME population are very weak (1–3% on average) and decrease with size. On average, the relationship between PDs and asset correlations is not negative, as assumed by Basel II, but positive, especially at the industry level, in the two countries. It is also possible to distinguish different segments inside the SMEs’ population: at least between very small and small SMEs and large SMEs.